2009
DOI: 10.1002/jmor.10810
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear structure and bone conduction in Spalax, Eospalax, and Tachyoryctes mole‐rats (Rodentia: Spalacidae)

Abstract: There is evidence that spalacine, tachyoryctine, and myospalacine mole-rats all communicate with conspecifics through a form of seismic signaling, but the route for the detection of these signals is disputed. It has been proposed that two unusual anatomical adaptations in Spalax allow jaw vibrations to pass to the inner ear via the incus and stapes: a pseudoglenoid (=postglenoid) fossa which accomodates the condylar process of the mandible, and a bony cup, supported by a periotic lamina, through which the incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Not only is the stapedio-vestibular articulation synovial in at least some bathyergids (this could not be assessed in all species) but the gap between stapes footplate and oval window is unusually wide (Fig 4A), which is expected to increase compliance still further. A very wide gap has previously been documented in the spalacid mole-rat Spalax [23] and the gerbil Gerbillurus [42]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only is the stapedio-vestibular articulation synovial in at least some bathyergids (this could not be assessed in all species) but the gap between stapes footplate and oval window is unusually wide (Fig 4A), which is expected to increase compliance still further. A very wide gap has previously been documented in the spalacid mole-rat Spalax [23] and the gerbil Gerbillurus [42]. …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, in these respects at least, it is Heterocephalus which shows the derived condition. It is not clear what the ancestral middle ear cavity morphology would be for the Ctenohystrica because this varies so much among different rodent species, even within the same family [23, 34, 42]. Heterocephalus is the smallest bathyergid: although cochlear coiling is unrelated to body size among mammals in general [41], it is possible that within the Bathyergidae the number of turns is somehow restricted by size, and that size affects middle ear cavity structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearing adaptation is reflected in morphological specializations of the ear structures (cf. Bruns et al 1988;Burda et al 1989Burda et al , 1992Müller et al , 1992Mason 2001;Schleich and Vassallo 2003;Lange et al 2005;Schleich et al 2006;Mason et al 2010). Frequency characteristics of vocalizations in subterranean rodents match the characteristics of hearing and the tunnel acoustics (Heth et al 1986;Pepper et al 1991;Capranica et al 1974;Credner et al 1997;Francescoli 1999;Veitl et al 2000;Schleich and Busch 2002;Knotková et al 2009).…”
Section: Introductionmentioning
confidence: 87%
“…63,65 The lenticular apophysis is usually attached to the long process of the incus by means of a thin, bony pedicle, which in many species appears to be flexible. 51,63,66 A finiteelement model of the cat incudo-stapedial articulation prompted the conclusion that the pedicle may in fact be more flexible than the articulation between the lenticular apophysis and the stapes itself. 64 Experimental evidence for flexibility within the mammalian middle ear From experiments using a capacitive probe, Møller 67 concluded that the malleus and incus of the cat are rigidly coupled at frequencies up to 2.5 kHz, at 'reasonably low' sound pressure levels.…”
Section: Mammalian Middle Earsmentioning
confidence: 99%